2021
DOI: 10.1002/adsc.202100812
|View full text |Cite
|
Sign up to set email alerts
|

Divergent Access to Benzocycles through Copper‐Catalyzed Borylative Cyclizations

Abstract: A copper‐catalyzed chemodivergent approach to five‐ and six‐membered benzocycles from dienyl arenes tethered with a ketone has been developed. Through proper choice of coordinating ligands and catalytic conditions, copper‐catalyzed borylative cyclization of a single dienyl arene can be diverted to two different pathways, leading to indanols and dihydronaphthalenols with high stereoselectivity. The chiral bidentate bisphosphine ligand (S,S)‐Ph‐BPE was optimal for asymmetric copper‐allyl addition to a tethered k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…Asymmetric intramolecular reductive cyclization of benz-tethered 1,3-dienes containing a ketone moiety proceeded via allylcopper intermediates and furnished a variety of cyclic tertiary alcohols containing two adjacent stereocenters in good yields with excellent enantio- and diastereoselectivities. 16 Mechanistic investigations using density functional theory revealed that ( Z )- and ( E )-allylcopper intermediates formed in situ from the diene and copper catalyst undergo isomerization and selective intramolecular allylation of the ( E )-allylcopper form of the major product through a six-membered boat-like transition state (Scheme 7).…”
Section: Asymmetric 12-addition Of Carbon Nucleophiles To Ketonesmentioning
confidence: 99%
See 1 more Smart Citation
“…Asymmetric intramolecular reductive cyclization of benz-tethered 1,3-dienes containing a ketone moiety proceeded via allylcopper intermediates and furnished a variety of cyclic tertiary alcohols containing two adjacent stereocenters in good yields with excellent enantio- and diastereoselectivities. 16 Mechanistic investigations using density functional theory revealed that ( Z )- and ( E )-allylcopper intermediates formed in situ from the diene and copper catalyst undergo isomerization and selective intramolecular allylation of the ( E )-allylcopper form of the major product through a six-membered boat-like transition state (Scheme 7).…”
Section: Asymmetric 12-addition Of Carbon Nucleophiles To Ketonesmentioning
confidence: 99%
“…The next year, the Yun group developed a copper-catalyzed chemo-divergent intramolecular allyl addition of dienyl arenes with a tethered ketone group. 18 Through a suitable choice of coordinating ligands and catalytic conditions, copper-catalyzed borylative cyclization of a single dienyl arene can be diverted to two different pathways. The chiral bidentate bisphosphine ligand ( S , S )-Ph-BPE was optimal for asymmetric copper-allyl addition to a tethered ketone via a boat-like transition state, whereas NHC ligands led to boron-allyl addition, producing indanols with high diastereoselectivities (Scheme 9).…”
Section: Asymmetric 12-addition Of Carbon Nucleophiles To Ketonesmentioning
confidence: 99%
“…These chemicals have been used in a variety of effective catalytic applications to produce a wide range of useful densely bifunctionalized products. In particular, an enantioselective intramolecular borylative cyclization of a diverse range of hydrocarbons with various electrophiles such as carbonyl, imine, and electron-withdrawing alkene for the construction of boron-containing carbocycles and heterocycles using copper catalysis is emerging as a key theme in modern synthesis [10,15,17]. Since the first report of copper-catalyzed borylative intramolcular cyclization of allylic carbonates by Ito and Sawamura [18], the cyclization reaction has grown in popularity and been extensively studied [19].…”
Section: Introductionmentioning
confidence: 99%
“…Most recently, Fañanás-Mastral et al reported a selective hydroboration of dendralenes . Other groups have developed LCu-Bpin addition reactions to 1,3-dienes as a first step in additional bond forming reactions such as Hoveyda’s multicomponent reactions, Cao and Liao’s imine addition, ketone additions, and Brown’s dual-Cu/Pd catalytic diene arylation reactions, , among others …”
mentioning
confidence: 99%